Quality of Chicken Patties with Different Levels of Tapioca Flour Prepared by Using Food Processer - Reddy, B. Ramachendra; Mandal, P.K.; Kasthuri , S.; Pal , U.K. (Journal of Meat Science, 2019)
A study was conducted to prepare spent hen meat patties by incorporation of tapioca flour and to compare the quality and economics of such patties processed by using food processor and bowl chopper. Chicken meat patties with 3% maida (control) and different levels of tapioca flour (3, 5 and 7%) prepared by using food processor were subjected to physico-chemical, chemical composition and sensory analysis. Results revealed that patties containing 5 and 7% tapioca flour had significantly (P<0.05) higher emulsion pH, emulsion stability (%) and cooking yield (%) than control. The sensory scores were desirable for appearance (7.30 to 7.57), flavour (7.03 to 7.33), texture (7.03 to 7.27), juiciness (6.90 to 7.20) and overall acceptability (7.10 to 7.43) on 8-point hedonic scale. No significant (P>0.05) differences were observed in sensory quality of patties containing different levels of tapioca flour, but 5% tapioca flour incorporated patties had non-significantly higher overall acceptability. The patties prepared with incorporation of 3 and 5% tapioca flour had significantly (P<0.05) higher protein and fat contents than patties containing 7% tapioca flour. Hence, formulation with 5% tapioca flour was select ed over 3% tapioca flour to replace more meat portion. The patties processed by using bowl chopper had significantly (P<0.05) higher emulsion stability (95.26%) and texture score (7.63) compared to patties processed by using food processor, but all other parameters remained unaffected. Quality of patties prepared by using food processor and bowl chopper were comparable. The cost of production of patties prepared by incorporating different levels of tapioca flour by replacing the meat decreased proportionately. Since the food processor is very cheap (Rs 5000), it is economical to prepare patties by incorporating 5% tapioca flour using food processor without affecting sensory and physico-chemical qualities for small scale production.